Degree of phosphorus saturation in agricultural loamy soils with a near‐neutral pH. (1st December 2014) - Renneson, M.; Vandenberghe, C.; Dufey, J.; Marcoen, J. M.; Bock, L.; Colinet, G.
Summary The degree of phosphorus saturation (DPS) represents the ratio of sorbed phosphorus (P) to the P sorption capacity (PSC) of soils. In some countries, DPS is used to evaluate the risk of P loss and surface water eutrophication. This study investigated DPS measurement and prediction in neutral loamy soils from Wallonia, Belgium. A total of 57 agricultural topsoil samples subject to diverse P management were evaluated. No satisfactory relationship could be found between PSC determined by a one‐point short‐term isotherm in the laboratory and the sum of aluminium and iron extracted by oxalate (Alox + Feox). The equation PSC = a Alox + b pHw appeared to be more appropriate for estimating PSC in the soils studied. These soils had a near‐neutral pH, and P fixation processes linked to the presence of calcium ions or carbonates were important. Comparisons of DPS with soil‐test P and water‐extracted P suggested that DPS could be a useful agronomic and/or environmental indicator. Our results also showed that DPS values between 20 and 30% corresponded to the agronomic optimum of soil P content. Consequently, DPS may be used as an indicator of P status in neutral soils, provided that the PSC assessment is adapted to the local soil characteristics. Résumé Le degré de saturation en phosphore dans les sols agricoles limoneux avec un pH proche de la neutralité. Le degré de saturation en phosphore (DPS) est un indicateur des risques de perte en phosphore (P) vers l'environnement utilisé dans de nombreux pays qui exprime la part de la capacité de sorption du P (PSC) réellement occupée par cet élément. L'objectif de cette étude est d'évaluer la faisabilité de l'utilisation du DPS pour les sols limoneux wallons présentant un pH proche de la neutralité. L'étude de 57 échantillons de surface de sols agricoles soumis à des modes de gestion contrastés n'a pas permis d'établir une bonne relation entre la PSC mesurée en laboratoire et la somme des teneurs en Al et Fe extraites à l'oxalate (Alox et Feox). L'utilisation d'une équation du type PSC = a Alox + b pHw semble plus appropriée dans les sols dont le pH est proche de la neutralité et où les carbonates de calcium interviennent dans la fixation du P. De plus, une comparaison du DPS avec les indicateurs agronomiques et environnementaux, P disponible et P extrait à l'eau, montre que DPS est compatible au système d'évaluation de la fertilité utilisé actuellement. Un DPS entre 20 et 30% correspond à une bonne fertilité du sol. Ainsi, le DPS peut être utilisé comme indicateur dans les sols neutres, à condition de préalablement adapter son calcul aux caractéristiques du sol.